Development and validation of a questionnaire to determine medical orders non-adherence: a sequential exploratory mixed-method study - Vahid Yazdi-Feyzabadi; Nouzar Nakhaee; Mohammad Hossein Mehrolhassani; Soheila Naghavi; Enayatollah Homaie Rad (BMC Health Services Research, 2021)
Abstract Background Patients’ non-adherence with medical orders of physicians in outpatient clinics can lead to reduced clinical effectiveness, inadequate treatment, and increased medical care expenses. This study was conducted to develop and validate a questionnaire to determine the reasons for patients’ non-adherence with physicians’ medical orders. Methods A sequential exploratory mixed-method study was conducted in two stages. The first stage comprised a qualitative stage to generate the primary items of the questionnaire. This stage provided findings of two sub-stages comprising a literature review and the findings of a qualitative conventional content analysis of 19 semi-structured interviews held with patients, physicians, and managers of the outpatient clinics in Kerman, an area located in southeastern Iran. The second stage comprised a quantitative study aiming evaluation of the instrument psychometric properties, including the face, content, construct, and reliability assessment of the questionnaire. Construct validity assessment was evaluated using exploratory factor analysis (EFA). The reliability assessment was done using assessing internal consistency (Cronbach’s alpha). To assess the construct validity of the questionnaire, four hundred and forty patients referred to outpatient clinics in Kerman were selected using stratified convenience sampling to fill out the questionnaire. The sample size was calculated using the Cochran formula. Qualitative and quantitative data were analyzed by MAXQDA 10 and Stata version 14, respectively. Results The primary items contained 57 items, of which 42 met the minimum acceptable value of 0.78 for item-level content validity index (I-CVI = 1 for 24 items and I-CVI = 0.8 for 18 items). Item-level content validity ratio (I-CVR) was confirmed for 18 items with a minimum acceptable value of 0.99 for five experts. Finally, 18 items obtained the acceptable value for both I-CVI and I-CVR indicators and were confirmed. Using EFA, four factors (intrapersonal-psychological, intrapersonal-cognitive, provider-related, and socio-economic reasons) with 18 items and Cronbach’s alpha coefficient of 0.70, 0.66, 0.73, and 0.71, respectively, were identified and explained 51% of the variance. The reliability of the questionnaire (r = 0.70) was confirmed. Conclusion The questionnaire with four dimensions is a valid and reliable instrument that can help determine the perceived reasons for non-adherence with medical orders in the outpatient services system.